2018
DOI: 10.1002/slct.201702643
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Versatile Route to Highly Functionalized Benzofuran Derivatives Using Biomimetic Oxygenation

Abstract: One‐pot green reactions useful for the synthesis of novel and potentially biologically active compounds have been developed using metaloporphyrin catalyzed oxidations of benzofurans. Minor variations of the reaction parameters allow direction of the reactivity (furan versus benzene ring) and the production of multifunctional 2,3‐dihydrobenzofurans, salicyl derivatives or an unusual dimerization product. These studies suggest pathways for the metabolic oxidation and activation of pharmaceuticals and other molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…From a comparison of the present results on the oxidation of benzofurans in the presence of Mn(III) porphyrins with those previously reported for biomimetic oxidation by an Fe(III) porphyrin in ethanol [28], it can be observed that the hydroxylation of the benzene ring is minimized (it is not observed in the isolated products) and a number of new coupling reactions and transformation pathways are detected.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…From a comparison of the present results on the oxidation of benzofurans in the presence of Mn(III) porphyrins with those previously reported for biomimetic oxidation by an Fe(III) porphyrin in ethanol [28], it can be observed that the hydroxylation of the benzene ring is minimized (it is not observed in the isolated products) and a number of new coupling reactions and transformation pathways are detected.…”
Section: Discussionsupporting
confidence: 72%
“…Previous work on the biomimetic oxidation of BF using iron porphyrins has shown that the products formed depend on the solvent evaporation temperature and on the Ox/S ratio [28]. Lower Ox/S ratios resulted in less degradation of the BF ring system.…”
Section: Benzofuran (Bf) Oxidation Reactionsmentioning
confidence: 91%
See 2 more Smart Citations
“…2-Aminopyrimidines with haloarene motifs (26,27) were synthesized efficiently, providing an orthogonal synthetic handle for conventional cross-coupling reactions. Moreover, the substrates bearing oxidatively labile functional groups, such as alkenyl, 101 benzofuranyl, 102 and amido, 103 were aminated in moderate to high yields (27−29).…”
mentioning
confidence: 99%